Intervention During Pregnancy to Reduce Excessive Gestational Weight Gain: A Randomized Controlled Trial. Issue 1 (March 2016) - Ronnberg, A.K.; Ostlund, I.; Fadl, H.; Gottvall, T.; Nilsson, K.
Abstract : ( BJOG. 2015;122(4):537–544) Excessive gestational weight gain (GWG) has a proven association with both negative obstetric outcomes and higher postpartum weight retention, making it a contributing factor to the prevalence of overweight and obesity among women and increasing the long-term risk of weight-associated diseases. Moreover, excessive GWG can influence the long-term health of the child by increasing the risk of childhood obesity.